Superbohaterki w kinie przed powstaniem Marvel Cinematic Universe. Historia adaptacji kobiecych kostiumów superbohaterskich - Klaudia Srul (Images)
The article focuses on changes within superhero comic book movie adaptations from 1941 (Adventures of Captain Marvel premiere) to 2008 (the creation of Marvel Cinematic Universe) in the aspect of designing female characters’ costumes. Author’s refelections are based on the article From the Top of the Cowl to the Tip of the Cape. The Cinematic Superhero Costume as Impossible by Dru H. Jeffries published in 2013 in „Cinephile: The Univesity of British Columbia’s Film Journal”. The author of the cited paper focuses on the topic of adapting male comic book characters’ costumes which is a starting point for the author of this article for in-depth analysis of this phenomenon including female superhero images.